(untitled) (Research, Society and Development, 2021)
The Santa Catarina state is inserted in the Atlantic Forest Biome, an ecosystem in which the application of environmental legislation has been the subject of intense technical-legal discussions. This study aimed to evaluate the impacts of applying the Forest Code (CF) and the Atlantic Forest Law (LMA) on riparian forest areas in rural properties in Santa Catarina. 100 rural properties were evaluated and the results showed that at least 65% of these properties meet the requirements of Legal Reserve, which for the state is defined at 20%. With the CF application, it’s observed that in 77 properties, the riparian forest areas occupy less than 10% of the total area of ​​the property. With the LMA application, this number drops to 24 properties. With the crossing of information from the productive area of ​​rural properties and the production area within the riparian forest area, the results show that by applying the CF, 80 properties show a reduction in the productive area by up to 10%. For the value of loss of the productive area of ​​up to 20%, the number of properties reaches 95. With the LMA application, the loss of up to 10% of the productive area drops to 16 properties. With the application of this law, 55% of the properties have a production area reduction greater than 20%. The application of laws brings different impacts on rural properties, with the LMA having a greater character of environmental preservation and, consequently, impacts more strongly in the reduction of productive areas.